Progression of science learning during transition from primary to secondary school - Mohd Fadzil, H.; Mohd. Saat, R. (2011)
School transition is a challenging process for students whereby they have to adapt with social issues to fit into new environment. Students themselves are experiencing a dramatic process of transformation from child to young adult stage. Although most of the pupils experience a smooth and successful transition and be able to adapt to their new learning environment, some of them find that transition is very difficult and problematic especially for those who are considered to be "at-risk". Previous research have shown a significance negative impact on students' attitude and attainment towards science learning, during the phase of transition from primary to secondary school. This phenomenon can be exhibited by decline in achievement and eroded interest in learning science. For Science Education, negative attitudes toward science subject are not only problematic for the students individually but it can also affect the nation's scientific and technological literacy and development of future scientist. School needs to response to these changes. To confront these issues and be effective and efficient in teaching process, school and teacher as an educational institution should provide vast opportunities far students to explore the content of science knowledge by establishing an encouraging, supportive and conducive atmosphere.